2019
DOI: 10.1093/europace/euz221
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest due to idiopathic ventricular fibrillation in patients with normal electrocardiograms: results from a multicentre long-term registry

Abstract: Aims  To define the clinical characteristics and long-term clinical outcomes of a large cohort of patients with idiopathic ventricular fibrillation (IVF) and normal 12-lead electrocardiograms (ECGs). Methods and results Patients with ventricular fibrillation as the presenting rhythm, normal baseline, and follow-up ECGs with no signs of cardiac channelopathy including early repolarization or atrioventricular conduction abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
3
29
2
Order By: Relevance
“…We identified that repeated cardiac arrest at index SCA increases the risk of appropriate ICD therapy and ERP in baseline ECG was not associated with an increased risk of appropriate ICD therapy. With only one traumatic noncardiological death in the follow‐up period the long‐term prognosis of IVF is good, which is consistent with other studies 5–7 …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We identified that repeated cardiac arrest at index SCA increases the risk of appropriate ICD therapy and ERP in baseline ECG was not associated with an increased risk of appropriate ICD therapy. With only one traumatic noncardiological death in the follow‐up period the long‐term prognosis of IVF is good, which is consistent with other studies 5–7 …”
Section: Discussionsupporting
confidence: 90%
“…In a recent study by Blom et al, 3 all conduction disturbances among IVF patients was pooled, and was found to increase risk of appropriate ICD therapy. Currently most studies include patients with LBBB in the IVF cohort, 3,5,9 however, this might change in the future 3,7 . Yet, in the present study we did not find any associations between conduction disturbances (neither individually or pooled) and the primary outcome, appropriate ICD therapy.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations